Sexual size dimorphism of the freshwater shrimp Macrobrachium jelskii (Miers, 1877) (Decapoda: Palaemonidae) and its relationship to Rensch's rule. Issue 2 (2nd April 2020) - Nascimento, Whandenson M.; De Lucena, Isis C.; Macedo, Rayury S.; Pinheiro, Allysson P.
ABSTRACT: Rensch's rule attempts to explain the evolutionary processes that have resulted in the current patterns of sexual size dimorphism of several taxa. This rule predicts that sexual size dimorphism increases according to the average body size, when males are larger, decreasing when females are the largest sex. In decapod crustaceans, the general pattern of sexual size dimorphism is males with hypertrophied structures used in agonistic disputes, and females with a greater expansion of the abdominal chamber. We analyzed sexual size dimorphism of the freshwater shrimp Macrobrachium jelskii and its relationship to Rensch's rule, as well as the relative growth between the sexes, for subpopulations from the Rosário reservoir in Ceará state, Brazil. The results of sexual size dimorphism show that females are morphometrically larger than males. Such a pattern of sexual dimorphism probably results from the selection of female fecundity, giving them greatest fecundity. This pattern indicates a female-biased SSD for this species, supported by what is proposed in Rensch's rule. In the relative growth analysis, the males and females showed negative allometry of the cheliped. The absence of cheliped hypertrophy in males may indicate the presence of 'pure-search' reproductive behaviour, thus, no agonistic disputes for females.